2004
DOI: 10.1097/01.inf.0000129690.35341.8d
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated Costs of Hospitalization for Respiratory Syncytial Virus Infection in Young Children at Risk

Abstract: RSV hospitalization costs were substantial, especially of specific high risk groups. Anticipated mean hospitalization costs of groups of children at risk for RSV hospitalization, but not yet hospitalized, could well be estimated with 4 child characteristics (age, gestational age, birth weight and BPD). These estimated costs can be used for economic analyses of preventive strategies for severe RSV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…The epidemiology of RSV shows a recurrent seasonal incidence pattern, similar to that of influenza, with an incidence peak in the winter months [3][4][5][6][7]. A previous RSV-infection may provide transient protection but does not prevent subsequent infections later on in life [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The epidemiology of RSV shows a recurrent seasonal incidence pattern, similar to that of influenza, with an incidence peak in the winter months [3][4][5][6][7]. A previous RSV-infection may provide transient protection but does not prevent subsequent infections later on in life [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Given the disease burden in the first year, vaccination was considered as early as possible. For a three-dose schedule vaccination was considered for infants [5,6] at the ages of 0, 1 and 3 months with vaccine efficacies of 30%, 60% and 75%, respectively. For a two-dose schedule, vaccination was considered at 0 and 3 month of age with vaccine efficacies of 30% and 70%.…”
Section: Vaccine Efficacy and Vaccination Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 85% of all children experiencing RSV hospitalization are born at term or later [33,135]. As shown in Paes et al [151], the model developed in Sampalis et al [146] cannot accurately predict RSV hospitalization or ED visit for term infants.…”
Section: Predicting Rsv Hospitalizationmentioning
confidence: 99%
“…For an individual patient to be admitted for RSV infection, Rietveld et al [135] developed a linear regression model to predict hospitalization cost, with an R 2 of 8% indicating low prediction accuracy. Fieldston et al [136] showed that zip code-based median annual household income is a predictor of hospitalization cost for bronchiolitis patients.…”
Section: Predicting Hospitalization Costmentioning
confidence: 99%